2022
DOI: 10.21608/epsj.2022.278520
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Using Ginger (Zingiber Officinale) in Laying Quail Diets on Egg Production, Egg Quality and Blood Parameters

Abstract: This study was carried out to evaluate the effect of using ginger (Zingiber officinale) in laying quail diets on egg production, egg quality and blood parameters. A total of 120 female quails at 10-weeks old were used with four treatment groups, in three replicates for each treatment, and 10 birds per replicate. The first group (control) was fed a basal diet. Second, third, and fourth treatments were fed on diets containing ginger roots powder at levels of 0.25, 0.5, and 0.75% of the diet. Egg production and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
2
0
0
Order By: Relevance
“…Also, using ginger reduced serum LDL and total cholesterol levels while raising HDL levels across the board compared to the control group. Our findings concur with Salmanzadeh (2015) , Zewail et al (2016) , Swain et al (2017) , Herve et al (2018) , Herve et al (2019) , Asghar et al (2021) , El-Kashif and Roshdy (2022) all described that ginger significantly reduced total cholesterol, HDL, and LDL. Due to ginger's high amount of unsaturated fatty acids, which might increase intestinal cholesterol release, plasma cholesterol levels may have decreased.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, using ginger reduced serum LDL and total cholesterol levels while raising HDL levels across the board compared to the control group. Our findings concur with Salmanzadeh (2015) , Zewail et al (2016) , Swain et al (2017) , Herve et al (2018) , Herve et al (2019) , Asghar et al (2021) , El-Kashif and Roshdy (2022) all described that ginger significantly reduced total cholesterol, HDL, and LDL. Due to ginger's high amount of unsaturated fatty acids, which might increase intestinal cholesterol release, plasma cholesterol levels may have decreased.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that adding ginger and frankincense oil to the diets of laying quail birds improved various periods of trial egg production characteristics. Our results are partly in line with those of El-Kashif and Roshdy (2022) , who found that egg production and number were considerably ( P ≤ 0.05) greater in treatments receiving feed having various grades of ginger root than in the control group. Along the same lines, egg weight and mass were considerably higher in the same treatments over 3 age phases and the entire reproductive period ( P ≤ 0.05).…”
Section: Discussionsupporting
confidence: 92%